Lower prevalence of hypertension, hypercholesterolemia, and diabetes in marathoners - Williams, P. T. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To test whether the prevalence of hypertension, hypercholesterolemia, and diabetes declines with marathon participation independent of annual running mileage.